Scrivere cambiando, cambiare scrivendo. Il rapporto ricercatore/attore nello studio dei movimenti sociali - Bertuzzi, Niccolò (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
Is it possible a value-free social research and without an ethical/political involvement of the researcher? If so, is it desirable? After a brief excursus on the origins of the sociological debate to be sought in anthropology emancipated from colonial discipline, the engaged/detached dichotomy will be recalled, along with some research programs that presuppose (even if in different ways) the involvement of the researcher. In the second part of the article, the attention will be focused on the specific sector of social movements studies, in which these issues assume central importance. Finally, we will take into account some empirical researches, to make the previously issues tangible. The reference will be to the relationship with the social actors and the issues they refer to, as emerged in three case studies: on the No-Expo Network, on the animal rights movement and on the relationship between movement activists and the European Union.